POPULASI DAN HABITAT LUTUNG JAWA (Trcyphitecus auratus E. Geoffrey 1812) DI RESORT BALANAN, TAMAN NASONAL BALURAN - Wahyu Indah Astriani; Harnios Arief; Lilik Budi Prasetyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Baluran National Park is a Nature Conserved Area which is one of the habitat of javan langur, however, its data is very limited. The objectives of the research is to study population and its key habitat component. The observation had been done in March-April 2015. Population of javan langur was estimated using Concentration Count Method. The result showed that there were 93 individuals (6 groups) with average size 15,5 ± 5,381. The existence of javan langur in Balanan Resort was supported by biotic factor, including the vegetation for their feeds and cover, such as Walikukun (Schoutenia ovata) dan Pilang (Acacia leucophloea), abiotic factor including altitude, slope, distance from river and distance from disturbance (road and villages). With regard with the habitat component, there are 4 factors of the characteristic habitat that influence, namely biotic factors of regeneration vegetations, abiotic factors, physics factors of vegetations, and biotic factors of climax vegetations. Keyword: abiotic, biotic, habitat, Javan Langur, population